Business process outsourcing : the competitive advantage - Click, Rick L. (John Wiley & Sons, 2005)
Annotation Business Process Outsourcing (BPO) is becoming the new revolution as company's of all sizes are seeking to take advantage of this source of competitive advantage. This book provides a step-by-step approach to understanding the application of Business Process Outsourcing, assessing the BPO opportunity in the company, and then managing the transition to BPO. It serves as a guide to implementing BPO and as a reference source to solving the variety of issues that may arise during a BPO initiative. Each chapter features a case study, insight from a practitioner, focus on how BPO affects people, and ethical considerations.* Discusses both the how and why of business process outsourcing with a straightforward "how to" approach.* Provides managers with the tools to analyse the BPO opportunities for their own firms, as well as techniques and strategies for managing a BPO initiative.* Empowers businesses of all sizes to take advantage of this all-encompassing business revolution